2015
DOI: 10.17159/2222-3436/2015/v18n1a4
|View full text |Cite
|
Sign up to set email alerts
|

Economic inequality as a source of interpersonal violence: Evidence from Sub-Saharan Africa and South Africa

Abstract: This article examines whether the close association of income inequality and violence identified for high income countries applies also to sub-Saharan Africa and, in particular, to South Africa. Cross sectional analysis across sub-Saharan countries provided no evidence of such an association. However, using homicide rates and several measures of inequality across South Africa's 52 districts does provide evidence of a significant positive relationship between homicide rates and expenditure inequality. A one per… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
12
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 22 publications
(12 citation statements)
references
References 15 publications
0
12
0
Order By: Relevance
“…The results highlighted the need for pro-poorness of growth reforms that would be helpful to lowering the crime rates in Latin American countries. Harris and Vermaak (2015) considered the relationship between expenditures' inequality and IHRe across 52 districts of South Africa and found that while keeping other district features constant, inequality does appear as a strong dominant player to induce IHR. The rational income distribution along with broad-based EG may play a vital role to reduce IHR in South Africa.…”
mentioning
confidence: 99%
“…The results highlighted the need for pro-poorness of growth reforms that would be helpful to lowering the crime rates in Latin American countries. Harris and Vermaak (2015) considered the relationship between expenditures' inequality and IHRe across 52 districts of South Africa and found that while keeping other district features constant, inequality does appear as a strong dominant player to induce IHR. The rational income distribution along with broad-based EG may play a vital role to reduce IHR in South Africa.…”
mentioning
confidence: 99%
“…South African adolescents live in a context characterised by high levels of exposure to violence. The homicide rate in the country is 5 times the global average with the highest victimisation rates seen in young men aged 15-29 years (Harris & Vermaak, 2015;Seedat van Niekerk, Jewkes, Suffla, & Ratele, 2009;Ward et al, 2012). The rate of homicide of women by an intimate partner is 6 times the global average with women between the ages of 14 and 44 years being at most risk (Gass, Stein, Williams, & Seedat, 2011).…”
mentioning
confidence: 99%
“…One of the main factors of inequality in Africa is the unequal distribution of national resources (Harris and Vermaak, 2015). Research found that, quality education and increased productivity are powerful tools for reducing poverty, but if not accompanied by progressive taxation and well-targeted social protection could accelerate income disparities.…”
Section: Literature Reviewmentioning
confidence: 99%